Catch-up Possibility of Vietnam’s Industries and Firms as Latecomers - Huyen Trang, Do (VNU Journal of Science: Policy and Management Studies, 2023)
Growth in some parts of Asia stayed promising even in the challenging circumstances. Despite difficulties posed, Vietnam as well as other ASEAN neighbours were able to maintain a positive growth rates. In fact, some of the top export areas of the country have not shown signs of being majorly impacted by the challenging circumstances. It was rather the strategic movement as well as (technological) capability accumulation of firm that matter the most. This paper looks at the intersection between OEM-ODM-OBM trajectory and the current window of opportunities to see if a possibility of securing a leading export position exists.